RAGAM DAN ALTERNATIF PENGEMBANGAN SUMBER PENDAPATAN PENDIDIKAN: ANALISIS PENGELOLAAN DANA ABADI UNIVERSITAS INDONESIA TAHUN 2021-2024 - Yuniawan, Eko; Umami, Lailia Hanif; Munadi, Muhammad (STKIP Pesisir Selatan, 2025)
This research aims to investigate the extent of the management of the endowment fund of the University of Indonesia and its development between 2021 and 2024, while also seeking alternatives to increase the university's financial resources as government funding diminishes. The technique used is qualitative, with the consolidated financial statements of the University of Indonesia as the main source, along with other official documents that typically accompany audits. Field findings indicate that the total value of the endowment fund has consistently grown, from Rp 114.8 billion at the end of 2021 to Rp 136.8 billion four years later, an increase of nearly 19.16 percent—equivalent to an average of 6.4 percent per year. The largest contributor comes from the Purnomo Yusgiantoro Foundation, contributing 36.5 percent in 2024, followed by the alumni fund which provided 28.9 percent, plus contributions from corporations and other donors. The accumulated funds are primarily allocated for scholarships, accounting for 58.3 percent; cross-disciplinary research 15.6 percent; and the enhancement of academic infrastructure 22.1 percent. The researcher notes that the management of the funds is conducted transparently and professionally—together with BNI Asset Management, the average annual return is at 9.8 percent, surpassing prolonged inflation.